Metagenomic analysis of the soil microbial composition and salt tolerance mechanism in Yuncheng Salt Lake, Shanxi Province - Zeng, Feifeng; Zhu, Yonghong; Zhang, Dongling; Zhao, Zengqiang; Li, Quansheng; Ma, Panpan; Zhang, Guoli; Wang, Yuan; Wu, Shenjie; Guo, Sandui; Sun, Guoqing (Frontiers in Microbiology, 2022)
The soil in Yuncheng Salt Lake has serious salinization and the biogeographic environment affects the composition and distribution of special halophilic and salt-tolerant microbial communities in this area. Therefore, this study collected soils at distances of 15 m, 30 m, and 45 m from the Salt Lake and used nonsaline soil (60 m) as a control to explore the microbial composition and salt tolerance mechanisms using metagenomics technology. The results showed that the dominant species and abundance of salt-tolerant microorganisms changed gradually with distance from Salt Lake. The salt-tolerant microorganisms can increase the expression of the Na+/H+ antiporter by upregulating the Na+/H+ antiporter subunit mnhA-G to respond to salt stress, simultaneously upregulating the genes in the betaine/proline transport system to promote the conversion of choline into betaine, while also upregulating the trehalose/maltose transport system encode genes to promote the synthesis of trehalose to resist a high salt environment.